Research on rural lodging design under the concept of culture and ecology - Yan YaoYao; Tan Huijie (SHS Web of Conferences)
With the rise of rural tourism, rural lodging has become a popular choice of accommodation. However, many rural lodgings in the design of the lack of regional and uniqueness, can not reflect the local cultural characteristics, the regional landscape and the construction of rural lodgings can not be a good organic integration, homogenisation is serious. This paper mainly takes the concept of culture and ecology as the theoretical basis, and explores the existence of regional cultural resources and natural resources in the expression of rural lodging design.